P3.082 Incidence of Congenital Syphilis in Paraguay. (13th July 2013) - Aranda, C; Aguilar, G; Suarez, Z; Munoz, S; Fusillo, C; Kawabata, A
Abstract : Background: The objective was to determine the incidence of congenital syphilis cases in the public health sector of Paraguay in 2010. Methods: observational, descriptive, retrospective study of newborns of the services of the country's public health sector excluding the Chaco region. The sample was obtained through two stage cluster sampling. The unit of analysis are the newborns. Results: Of 6739 newborn registries examined, 69 met the criteria for definition of congenital syphilis case. The incidence of congenital syphilis was 10.23 per 1000 live births. 73.9% of the mothers of the children with congenital syphilis had attended the prenatal check-ups. In 37.7% of pregnant women syphilis was diagnosed less than a month before childbirth followed by 26.1% that were diagnosed during labour and did not receive treatment. Two of the 69 newborns died. Conclusion: Congenital syphilis continues to be an important public health problem in Paraguay. The majority of the women with children with congenital syphilis attended prenatal check-ups, indicating missed opportunities for the health services. The high incidence of the congenital syphilis is an indicator of the quality of the health services and this highlights the need to consider syphilis among the priority problems in Paraguay, and to intensify actions for its control.